Participación ciudadana en la gestión del Gobierno Autónomo Descentralizado del Cantón Junín período 2014-2018 - Loor Cedeño, Leandro Antonio (2020)
The Magna Carta maintains that the role of Citizen Participation is a right that citizens have to directly intervene in decisions that are considered specific in a public function of the State. The present study was carried out in the GAD of the Junín canton with the objective of determining the citizen participation mechanisms of the GAD of the Junín canton and thus determining the regulatory public policies and then being compared with other laws that promote said activity. To comply with the objectives of the investigation, the regulatory public policies of the entity were examined and then compared with the other laws applied by citizen participation in the country; subsequently, citizen participation mechanisms were determined through the application of an interview with the director of the department where he established that citizen participation needs to be strengthened in Junín, since in other past administrations participation was not seen as an instance of contribution from public value, then a survey was carried out that allowed to know flaws and strengths of the actors, indicating a deficiency of participation in the application of mechanisms also breach of the law. Finally, the popular initiatives of civil society and their impact on the management of the GAD of the Junín canton were evaluated, where it was determined that only 14% participate in cantonal assemblies; Thus, the mechanisms have not served much to prioritize public works and citizen participation in projects.